High-strength and high-toughness PHA plant fiber composite material and preparation method thereof

Through the combination of long-chain fatty acid modified palm fiber and nanotitanium dioxide, the compatibility problems of fiber and PHA and ultraviolet degradation problems in PHA plant fiber composite materials are solved, significantly improving the mechanical properties and ultraviolet resistance of the material, and extending the use life.

CN119264626AActive Publication Date: 2025-01-07NINGBO HOMELINK ECO ITECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411794326.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-07
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In PHA plant fiber composite, it is difficult to mix evenly with PHA materials, resulting in room for improvement in mechanical properties and is prone to oxidation and degradation under ultraviolet light, shortening service life.

Method used

Long-chain fatty acid modified palm fiber is used to combine with nanotitanium dioxide to improve the compatibility of fibers and PHA through esterification reaction, and the nanotitanium dioxide absorbs and reflects ultraviolet rays and eliminates free radicals to improve the resistance to ultraviolet rays.

Benefits of technology

It significantly improves the strength, toughness and UV resistance of PHA plant fiber composites and extends its service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of polymer composite materials, in particular to a high-strength and high-toughness PHA plant fiber composite material and a preparation method thereof. The high-strength and high-toughness PHA plant fiber composite material comprises the following raw materials in parts by mass: 60-80 parts of polyhydroxyalkanoate, 20-30 parts of modified palm fibers, 1-5 parts of a plasticizer and 2-4 parts of a nucleating agent, and the modified palm fibers are long-chain fatty acid modified palm fibers. The PHA plant fiber composite material provided by the invention has excellent strength and toughness, also has excellent ultraviolet resistance, and also maintains excellent degradability of the PHA plant fiber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer composite materials, and more specifically, to a high-strength and high-toughness PHA plant fiber composite material and a preparation method thereof. Background Art

[0002] PHA, also known as polyhydroxyalkanoate, is a type of bio-based polymer material synthesized by microorganisms in a nutrient-rich environment. It has excellent biodegradability and can be completely degraded into titanium dioxide and water by microorganisms in the natural environment, thus avoiding the problem of traditional plastics accumulating in the environment. At the same time, PHA also has good plasticity and thermoplasticity, and can be formed by injection molding, extrusion and blow molding.

[0003] However, the mechanical properties of PHA are poor, even lower than other biodegradable materials such as polylactic acid. Therefore, toughening and strengthening of PHA is the top priority of current PHA research. At present, toughening and strengthening of PHA is carried out by using fiber reinforcement. Compared with synthetic fibers, plant fibers not only have excellent toughening and strengthening effects, but can also be degraded under the action of microorganisms, thus not affecting the biodegradable properties of PHA.

[0004] However, there are a large number of hydroxyl groups on the surface of plant fibers, which have strong hydrophilicity, while PHA molecules are low-polar materials. This polarity makes it difficult to mix plant fibers and PHA materials evenly when blended, that is, there is an interface, which leads to the mechanical properties of the prepared PHA plant fiber composites still have room for improvement. Summary of the invention

[0005] In order to improve the defect that plant fibers and PHA are difficult to mix uniformly in conventional PHA plant fiber composite materials, the present application provides a high-strength and high-toughness PHA plant fiber composite material and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-strength and high-toughness PHA plant fiber composite material, which adopts the following technical solution: A high-strength and high-toughness PHA plant fiber composite material comprises the following raw materials in parts by weight: 60-80 parts of polyhydroxyalkanoate, 20-30 parts of modified palm fiber and 2-4 parts of lubricant, wherein the modified palm fiber is palm fiber modified with long-chain fatty acid.

[0007] The cellulose of palm fiber is long, so it has extremely good strength and toughness. However, there are a large number of hydroxyl groups on the surface of palm fiber, and palm fiber also has a high degree of intramolecular hydrogen bonding, which makes the interface wettability and adhesion between palm fiber and PHA very poor.

[0008] After the long-chain fatty acid modification, the carboxyl group in the long-chain fatty acid reacts with the hydroxyl group on the surface of the palm fiber under the action of a catalyst to undergo an esterification reaction. While consuming the hydroxyl group, the long-chain fatty acid can also be connected to the surface of the palm fiber to form an ester, thereby achieving extremely good compatibility with polyhydroxyalkanoates, reducing the generation of interfaces, and enabling the PHA plant fiber composite material to obtain better strength and toughness.

[0009] Preferably, the method for preparing the modified palm fiber comprises the following steps: S1. First, wash the palm fiber with deionized water for 3-5 times, dry it at 30-50°C and cut it into pieces. The length of the palm fiber is 5-10 mm. S2, soaking the palm fiber in deionized water, then adding potassium hydroxide solution, stirring for 2-4 hours, and then drying the palm fiber to obtain alkaline palm fiber; S3. Add long-chain fatty acids and stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 80-90° C. for 4-8 hours, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

[0010] Preferably, the method for preparing the modified palm fiber comprises the following steps: S1. First, wash the palm fiber with deionized water for 3-5 times, dry it at 30-50°C and cut it into pieces. The length of the palm fiber is 5-10 mm. S2, soaking 6-10 g of palm fiber in 80-90 ml of deionized water, then adding 1-3 ml of 25 wt% potassium hydroxide solution, stirring for 2-4 hours, and then drying the palm fiber to obtain alkaline palm fiber; S3. Add 2-4g of long-chain fatty acid and 0.2-0.4g of stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 80-90°C for 4-8h, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

[0011] When the components of the modified palm fiber are added in the above-mentioned amounts, the hydroxyl content on the surface of the palm fiber will be relatively less, and more long-chain fatty acid esters will be attached to the surface of the palm fiber, thereby promoting better compatibility between the palm fiber and polyhydroxyalkanoates, which is manifested in that the PHA plant fiber composite material obtains better strength and toughness.

[0012] Preferably, nano titanium dioxide is also added to S3.

[0013] When PHA plant fiber composites are exposed to strong ultraviolet rays, the ultraviolet rays will excite the chemical bonds in PHA to form free radicals, thereby causing the PHA molecular chains to break, and then causing the PHA plant fiber composites to oxidatively degrade. However, this degradation makes the PHA plant fiber composites prone to unnecessary degradation during actual use, resulting in a shorter service life of the PHA plant fiber composites.

[0014] Nano-titanium dioxide can absorb and reflect ultraviolet rays and eliminate the generation of free radicals. At the same time, the surface of palm fiber contains a large number of holes, which can effectively load nano-titanium dioxide, thereby effectively improving the anti-ultraviolet performance of PHA plant fiber composite materials.

[0015] Preferably, the step of S3 is: Add 2-4g long-chain fatty acid and 0.2-0.4g stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 80-90°C for 4-8h, then add 1-2g nano titanium dioxide, mix and stir again for 30-60min, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

[0016] Preferably, in S3, the nano titanium dioxide is first modified by vinyltriethoxysilane, and the long-chain fatty acid is an unsaturated long-chain fatty acid DPA-FITC.

[0017] Although palm fiber can load nano-titanium dioxide through its pores, purely physical adsorption loading may still lead to the detachment and agglomeration of nano-titanium dioxide, thereby affecting the UV resistance of PHA plant fiber composites.

[0018] When nano-titanium dioxide is first modified with vinyltriethoxysilane, the double bonds in vinyltriethoxysilane reconnect with the double bonds in unsaturated long-chain fatty acids, thereby enabling the nano-titanium dioxide bonds to be connected to the matrix of the PHA plant fiber composite material, further reducing the possibility of nano-titanium dioxide detachment, effectively improving the dispersibility of nano-titanium dioxide in the PHA plant fiber composite material, and indirectly improving the UV resistance of the PHA plant fiber composite material.

[0019] Preferably, the mass ratio of the vinyltriethoxysilane to the nano-titanium dioxide is 1:(1:3).

[0020] When vinyl triethoxysilane and nano titanium dioxide are in the above mass ratio, the prepared PHA plant fiber composite material will have better anti-ultraviolet performance.

[0021] Preferably, the step of S3 is: Add 2-4g long-chain fatty acid and 0.2-0.4g stannous oxalate to alkaline palm fiber, stir evenly, and then react at 80-90°C for 4-8h, then add nano titanium dioxide modified by vinyltriethoxysilane, the addition amount of nano titanium dioxide is 1-3g, and 0.2-0.4g azobisisobutyronitrile is added at the same time, mixed and stirred at 70-90°C for 1-2h, and then 0.2-0.4g triethylamine is added for neutralization, cooled to room temperature, and finally washed and dried to obtain modified palm fiber.

[0022] In a second aspect, the present application provides a method for preparing a high-strength and high-toughness PHA plant fiber composite material, using the following technical solution: A method for preparing a high-strength and high-toughness PHA plant fiber composite material comprises the following steps: Step 1: First, the polyhydroxyalkanoate powder is dried at a temperature of 70-80° C. to control the water content of the polyhydroxyalkanoate to be less than 30 PPM; Step 2: Mixing polyhydroxyalkanoate powder, modified palm fiber and lubricant, and then transferring to a twin-screw extruder for melt extrusion and drying to obtain a high-strength and high-toughness PHA plant fiber composite material; The parameters of the twin-screw extruder are as follows: melt temperature 180-190°C, screw speed 200-400r / min.

[0023] In summary, this application has the following beneficial effects: 1. Palm fiber has a long cellulose length, so it has excellent strength and toughness. However, there are a large number of hydroxyl groups on the surface of palm fiber, and palm fiber also has a high degree of intramolecular hydrogen bonding, which makes the interface wettability and adhesion between palm fiber and PHA very poor; After the long-chain fatty acid modification, the carboxyl group in the long-chain fatty acid reacts with the hydroxyl group on the surface of the palm fiber under the action of a catalyst to undergo an esterification reaction. While consuming the hydroxyl group, the long-chain fatty acid can also be connected to the surface of the palm fiber to form an ester, thereby achieving extremely good compatibility with polyhydroxyalkanoates, reducing the generation of interfaces, and enabling the PHA plant fiber composite material to obtain better strength and toughness.

[0024] 2. When the PHA plant fiber composite material is exposed to strong ultraviolet rays, the ultraviolet rays will stimulate the chemical bonds in the PHA to form free radicals, thereby causing the PHA molecular chain to break, and then causing the PHA plant fiber composite material to oxidatively degrade. However, this degradation makes the PHA plant fiber composite material prone to unnecessary degradation during actual use, resulting in a short service life of the PHA plant fiber composite material; Nano-titanium dioxide can absorb and reflect ultraviolet rays and eliminate the generation of free radicals. At the same time, the surface of palm fiber contains a large number of holes, which can effectively load nano-titanium dioxide, thereby effectively improving the anti-ultraviolet performance of PHA plant fiber composite materials.

[0025] 3. Although palm fiber can load nano-titanium dioxide through its pores, purely physical adsorption loading may still lead to the detachment and agglomeration of nano-titanium dioxide, thus affecting the UV resistance of PHA plant fiber composites; When nano-titanium dioxide is first modified with vinyltriethoxysilane, the double bonds in vinyltriethoxysilane reconnect with the double bonds in unsaturated long-chain fatty acids, thereby enabling the nano-titanium dioxide bonds to be connected to the matrix of the PHA plant fiber composite material, further reducing the possibility of nano-titanium dioxide detachment, effectively improving the dispersibility of nano-titanium dioxide in the PHA plant fiber composite material, and indirectly improving the UV resistance of the PHA plant fiber composite material. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with Examples 1-8 and Comparative Example 1.

[0027] raw material Polyhydroxyalkanoate Lana White; Palm fiber is commercially available; Lubricant calcium stearate CAS: 1592-23-0; Unsaturated long-chain fatty acid DPA-FITC Xinweichuang; Potassium hydroxide CAS: 1310-58-3; Stannous oxalate CAS: 814-94-8; Nano-titanium dioxide CAS: 13463-67-7; Vinyl triethoxysilane CAS: 78-08-0; Long-chain saturated fatty acid-stearic acid CAS: 57-11-4.

[0028] Example 1 A high-strength and high-toughness PHA plant fiber composite material comprises the following raw materials: 70g of polyhydroxyalkanoate, 25g of modified palm fiber and 3g of lubricant, wherein the modified palm fiber is palm fiber modified with long-chain fatty acid.

[0029] The preparation method of modified palm fiber comprises the following steps: S1. First, the palm fiber was washed with deionized water for 4 times, dried at 50°C and cut into pieces. The length of the palm fiber was 8 mm. S2, soaking 8 g of palm fiber in 90 ml of deionized water, then adding 2 ml of 25 wt% potassium hydroxide solution, stirring for 3 hours, and then drying the palm fiber to obtain alkaline palm fiber; S3. Add 3 g of unsaturated long-chain fatty acid DPA-FITC and 0.3 g of stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 90° C. for 6 h, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

[0030] The preparation method of the high-strength and high-toughness PHA plant fiber composite material comprises the following steps: Step 1: First, the polyhydroxyalkanoate powder is dried at a temperature of 70-80° C. to control the water content of the polyhydroxyalkanoate to be less than 30 PPM; Step 2: Mixing polyhydroxyalkanoate powder, modified palm fiber and lubricant, and then transferring to a twin-screw extruder for melt extrusion and drying to obtain a high-strength and high-toughness PHA plant fiber composite material; The parameters of the twin-screw extruder are as follows: melt temperature 190°C, screw speed 400r / min.

[0031] Example 2-3 The difference from Example 1 is that the addition amount of each component in the modified palm fiber is different, as shown in Table 1.

[0032] Table 1 Addition amount of each component of modified palm fiber in Example 1 and Examples 2-3 Example 1 Example 2 Example 3 Palm Fiber 8g 6g 10g 25wt% potassium hydroxide solution 2ml 3ml 1ml Unsaturated long chain fatty acids 3g 2g 4g Example 4 The difference from Example 1 is that nano titanium dioxide is also added to S3; The steps of S3 are: Add 3g of unsaturated long-chain fatty acid DPA-FITC and 0.3g of stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 90°C for 6h, then add 1.5g of nano titanium dioxide, mix and stir again for 45min, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

[0033] The difference from Example 4 is that the nano-titanium dioxide is first modified by vinyltriethoxysilane; The steps of S3 are: Add 3g of unsaturated long-chain fatty acid DPA-FITC and 0.3g of stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 90°C for 6h, then add nano-titanium dioxide modified with vinyltriethoxysilane, the vinyltriethoxysilane modification step is conventional mixing, the mass ratio of vinyltriethoxysilane to nano-titanium dioxide is 1:2, the amount of nano-titanium dioxide added is 2g, and 0.3g of azobisisobutyronitrile is added at the same time, mixed and stirred at 80°C for 2h, and then 0.3g of triethylamine is added for neutralization, cooled to room temperature, and finally washed and dried to obtain modified palm fiber.

[0034] The difference from Example 5 is that the mass ratio of vinyltriethoxysilane to nano-titanium dioxide is different, as shown in Table 2.

[0035] Embodiment 5-7 Table 2 Mass ratio of vinyl triethoxysilane to nano titanium dioxide in Examples 5-7 Example 5 Example 6 Example 7 Vinyltriethoxysilane 1 1 1 Nano Titanium Dioxide 2 1 3 Example 8 The difference from Example 1 is that the unsaturated long-chain fatty acid DPA-FITC is replaced by a saturated long-chain fatty acid-stearic acid.

[0036] Comparative Example 1 A PHA plant fiber composite material comprises the following raw materials: 70g of polyhydroxyalkanoate and 3g of lubricant.

[0037] The preparation method of the PHA plant fiber composite material comprises the following steps: Step 1: First, the polyhydroxyalkanoate powder is dried at a temperature of 70-80° C. to control the water content of the polyhydroxyalkanoate to be less than 30 PPM; Step 2: Mixing polyhydroxyalkanoate powder and lubricant, and then transferring to a twin-screw extruder for melt extrusion and drying to obtain a high-strength and high-toughness PHA plant fiber composite material; The parameters of the twin-screw extruder are as follows: melt temperature 190°C, screw speed 400r / min.

[0038] Performance testing 1. Tensile strength test Three samples were taken from Examples 1-3 and Comparative Example 1, respectively, and the tensile strength of the samples was tested according to GB / T1040-2024 “Test Method for Tensile Properties of Plastics”, and the average value was taken. The test data are shown in Table 3.

[0039] Table 3 Tensile strength of Examples 1-3 and Comparative Example 1 Tensile strength / MPa Tensile strength / MPa Example 1 79 Example 3 76 Example 2 74 Comparative Example 1 54 2. Anti-ultraviolet performance test Six samples were taken from each of Example 1 and Examples 4-8, and the tensile strength of three of the samples was tested according to GB / T1040-2024 "Test Method for Tensile Properties of Plastics", and the average value was taken and recorded as the original tensile strength; Then, refer to the fluorescent ultraviolet lamp exposure test method of GB / T 14522-2008 "Artificial weathering test method for plastics, coatings and rubber materials for mechanical industrial products - fluorescent ultraviolet lamp" to treat the remaining three samples with ultraviolet light, with an irradiation intensity of 0.68W / m2×nm, continuous illumination for 700h, blackboard temperature of 63℃, and no spraying conditions. Finally, refer to GB / T1040-2024 "Test method for tensile properties of plastics" to test the tensile strength of the three aged samples again, and take the average value, which is recorded as the aged tensile strength; Finally, the UV resistance rate is calculated, UV resistance rate = aging tensile strength / original tensile strength × 100%. The test data is shown in Table 4.

[0040] Table 4 Anti-ultraviolet performance of Example 1 and Examples 4-8 / % UV resistance UV resistance Example 1 53.7% Example 6 90.1% Example 4 85.6% Example 7 91.3% Example 5 93.9% Example 8 88.5% Referring to Example 1 and Comparative Example 1 and in combination with Table 3, it can be seen that the tensile strength of Example 1 is significantly improved compared with that of Comparative Example 1, which indicates that after the surface of the palm fiber is modified by the unsaturated long-chain fatty acid DPA-FITC, the mechanical properties of the prepared PHA plant fiber composite material will be significantly improved.

[0041] The reason is that the cellulose of palm fiber is long, so it has extremely good strength and toughness. However, there are a large number of hydroxyl groups on the surface of palm fiber, and palm fiber also has a high degree of intramolecular hydrogen bonding, which makes the interface wettability and adhesion between palm fiber and PHA very poor.

[0042] After the long-chain fatty acid modification, the carboxyl group in the long-chain fatty acid reacts with the hydroxyl group on the surface of the palm fiber under the action of a catalyst to undergo an esterification reaction. While consuming the hydroxyl group, the long-chain fatty acid can also be connected to the surface of the palm fiber to form an ester, thereby achieving extremely good compatibility with polyhydroxyalkanoates, reducing the generation of interfaces, and enabling the PHA plant fiber composite material to obtain better strength and toughness.

[0043] With reference to Examples 1-3 and in combination with Table 3, it can be seen that, relative to Example 1, the tensile strength of Examples 2-3 is slightly decreased, which indicates that when the components in the modified palm fiber are added in the amounts of Example 1, the prepared PHA plant fiber composite material will have better mechanical properties.

[0044] Referring to Example 1 and Example 4 and combining with Table 4, it can be seen that compared with Example 1, the anti-ultraviolet rate of Example 4 is significantly improved, which shows that the addition of nano-titanium dioxide can effectively improve the anti-ultraviolet performance of the PHA plant composite material.

[0045] The reason is that when PHA plant fiber composites are exposed to strong ultraviolet rays, the ultraviolet rays will stimulate the chemical bonds in PHA to form free radicals, which will cause the PHA molecular chain to break, and then cause the PHA plant fiber composites to oxidatively degrade. However, this degradation makes the PHA plant fiber composites prone to unnecessary degradation during actual use, resulting in a short service life of the PHA plant fiber composites. Nano-titanium dioxide can absorb and reflect ultraviolet rays and eliminate the generation of free radicals. At the same time, the surface of palm fiber contains a large number of holes, which can effectively load nano-titanium dioxide, thereby effectively improving the anti-ultraviolet performance of PHA plant fiber composite materials.

[0046] Referring to Example 4 and Example 5 and combining with Table 4, it can be seen that compared with Example 4, the UV resistance rate of Example 5 is further improved, which shows that the operation of modifying nano-titanium dioxide with vinyltriethoxysilane can further improve the UV resistance of the PHA plant composite material.

[0047] The reason is that although palm fiber can load nano-titanium dioxide through its pores, purely physical adsorption loading may still lead to the detachment and agglomeration of nano-titanium dioxide, thereby affecting the UV resistance of PHA plant fiber composites.

[0048] When nano-titanium dioxide is first modified with vinyltriethoxysilane, the double bonds in vinyltriethoxysilane reconnect with the double bonds in unsaturated long-chain fatty acids, thereby enabling the nano-titanium dioxide bonds to be connected to the matrix of the PHA plant fiber composite material, further reducing the possibility of nano-titanium dioxide detachment, effectively improving the dispersibility of nano-titanium dioxide in the PHA plant fiber composite material, and indirectly improving the UV resistance of the PHA plant fiber composite material.

[0049] Referring to Examples 5-7 and in combination with Table 4, it can be seen that, relative to Example 5, the UV resistance rates of Examples 6-7 are slightly decreased, which indicates that when the mass ratio of vinyltriethoxysilane to nano-titanium dioxide is the same as that of Example 5, the prepared PHA plant composite material will have better UV resistance.

[0050] Referring to Example 5 and Example 8 and in combination with Table 4, it can be seen that the anti-ultraviolet rate of Example 8 is significantly reduced compared with Example 5, which shows that the use of saturated long-chain fatty acids will lead to a significant decrease in the dispersibility of the nano-titanium dioxide and PHA plant fiber composite material compared with the use of unsaturated long-chain fatty acids. The reason is that there is no double bond on the long chain of the saturated long-chain fatty acid, and the nano-titanium dioxide is only connected to the palm fiber through the silane coupling effect of vinyltriethoxysilane. The connection effect is relatively insufficient, resulting in the nano-titanium dioxide being relatively easier to detach and the dispersibility being relatively insufficient, which ultimately manifests as a slight decrease in the anti-ultraviolet performance of the PHA plant fiber composite material.

[0051] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-strength and high-toughness PHA plant fiber composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of polyhydroxyalkanoate, 20-30 parts of modified palm fiber and 2-4 parts of lubricant, wherein the modified palm fiber is palm fiber modified with long-chain fatty acid.

2. The high-strength and high-toughness PHA plant fiber composite material according to claim 1, characterized in that: The preparation method of the modified palm fiber comprises the following steps: S1. First, wash the palm fiber with deionized water for 3-5 times, dry it at 30-50°C and cut it into pieces. The length of the palm fiber is 5-10 mm. S2, soaking the palm fiber in deionized water, then adding potassium hydroxide solution, stirring for 2-4 hours, and then drying the palm fiber to obtain alkaline palm fiber; S3. Add long-chain fatty acids and stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 80-90° C. for 4-8 hours, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

3. The high-strength and high-toughness PHA plant fiber composite material according to claim 2, characterized in that: The preparation method of the modified palm fiber comprises the following steps: S1. First, wash the palm fiber with deionized water for 3-5 times, dry it at 30-50°C and cut it into pieces. The length of the palm fiber is 5-10 mm. S2, soaking 6-10 g of palm fiber in 80-90 ml of deionized water, then adding 1-3 ml of 25 wt% potassium hydroxide solution, stirring for 2-4 hours, and then drying the palm fiber to obtain alkaline palm fiber; S3. Add 2-4g of long-chain fatty acid and 0.2-0.4g of stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 80-90°C for 4-8h, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

4. The high-strength and high-toughness PHA plant fiber composite material according to claim 2, characterized in that: Nano-titanium dioxide is also added to S3.

5. The high-strength and high-toughness PHA plant fiber composite material according to claim 4, characterized in that: The steps of S3 are: Add 2-4g long-chain fatty acid and 0.2-0.4g stannous oxalate to the alkaline palm fiber, stir evenly, and then react at 80-90°C for 4-8h, then add 1-2g nano titanium dioxide, mix and stir again for 30-60min, then cool to room temperature, and finally wash and dry to obtain modified palm fiber.

6. The high-strength and high-toughness PHA plant fiber composite material according to claim 4, characterized in that: In S3, the nano titanium dioxide is first modified by vinyltriethoxysilane, and the long-chain fatty acid is an unsaturated long-chain fatty acid DPA-FITC.

7. The high-strength and high-toughness PHA plant fiber composite material according to claim 6, characterized in that The mass ratio of the vinyl triethoxysilane to the nano titanium dioxide is 1:(1:3).

8. The high-strength and high-toughness PHA plant fiber composite material according to claim 6, characterized in that: The steps of S3 are: Add 2-4g long-chain fatty acid and 0.2-0.4g stannous oxalate to alkaline palm fiber, stir evenly, and then react at 80-90°C for 4-8h, then add nano titanium dioxide modified by vinyltriethoxysilane, the addition amount of nano titanium dioxide is 1-3g, and 0.2-0.4g azobisisobutyronitrile is added at the same time, mixed and stirred at 70-90°C for 1-2h, and then 0.2-0.4g triethylamine is added for neutralization, cooled to room temperature, and finally washed and dried to obtain modified palm fiber.

9. A method for preparing the high-strength and high-toughness PHA plant fiber composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: First, the polyhydroxyalkanoate powder is dried at a temperature of 70-80° C. to control the water content of the polyhydroxyalkanoate to be less than 30 PPM; Step 2: Mixing polyhydroxyalkanoate powder, modified palm fiber and lubricant, and then transferring to a twin-screw extruder for melt extrusion and drying to obtain a high-strength and high-toughness PHA plant fiber composite material; The parameters of the twin-screw extruder are as follows: melt temperature 180-190°C, screw speed 200-400r / min.

Citation Information

Patent Citations

  • Polyhydroxyalkanoate full-degradation composite material, preparation method and applications thereof

    CN102850741A

  • Degradable lightweight polyolefin composite for injection molding and preparation method of composite

    CN106317934A

  • Plant fiber-reinforced polyhydroxyalkanoate composite material and preparation method thereof

    CN107383818A

  • High-toughness full-degradable composite material

    CN110655769A

  • Bagasse fiber / PHA completely degradable composite material and preparation method thereof

    CN112358712A